Volume Of Solids of Revolution

Calculus Level 4

Let β \beta be a positive integer and x > 1 |x| > 1 .

Let f ( x ) = j = 0 x β + j + 1 x β + j x β + j x β + j + 1 f(x) = \sum_{j = 0}^{\infty} \dfrac{x^{\beta + j + 1} - x^{\beta + j}}{x^{\beta + j} * x^{\beta + j + 1}} and g ( x ) = 1 a x + b g(x) = \dfrac{1}{ax + b} .

Let V f V_{f} be the volume of the region formed when the curve f ( x ) f(x) is revolved about the x x -axis on [ 2 , ) [2,\infty) and V g V_{g} be the volume of the region formed when the curve g ( x ) g(x) is revolved about the x x -axis on [ 2 , ) [2,\infty)

If f ( 2 ) = g ( 2 ) f(2) = g(2) and V f = V g V_{f} = V_{g} and the volume V V of the region bounded by the curves f ( x ) f(x) and g ( x ) g(x) when revolved about the x x -axis on ( , 2 ] (-\infty,-2] can be expressed as V = α α ( β w ) π ( α β w ) ( α α β λ ) ( α α β w ) V = \dfrac{\alpha^{\alpha} (\beta - w)\pi}{(\alpha\beta - w)(\alpha^{\alpha}\beta - \lambda) (\alpha^{\alpha\beta - w})} , where α , w \alpha, w and λ \lambda are coprime positive integers, find α + w + λ \alpha + w + \lambda .

I used β = 2 \beta = 2 for the above graph.


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Jul 22, 2018

Let x > 1 |x| > 1 .

f ( x ) = j = 0 x β + j + 1 x β + j x β + j x β + j + 1 = j = 0 x β + j ( x 1 ) x 2 ( β + j ) x = x 1 x β + 1 j = 0 ( 1 x ) j = ( x 1 x β + 1 ) ( x x 1 ) = 1 x β f(x) = \sum_{j = 0}^{\infty} \dfrac{x^{\beta + j + 1} - x^{\beta + j}}{x^{\beta + j} * x^{\beta + j + 1}} = \sum_{j = 0}^{\infty} \dfrac{x^{\beta + j} (x - 1)}{x^{2(\beta + j)} * x} = \dfrac{x - 1}{x^{\beta + 1}} \sum_{j = 0}^{\infty} (\dfrac{1}{x})^{j} = (\dfrac{x - 1}{x^{\beta + 1}}) (\dfrac{x}{x - 1}) = \boxed{\dfrac{1}{x^{\beta}}}

Let g ( x ) = 1 a x + b g(x) = \dfrac{1}{ax + b} .

f ( 2 ) = g ( 2 ) 2 a + b = 2 β f(2) = g(2) \implies \boxed{2a + b = 2^{\beta}}

V f = π 2 ( f ( x ) ) 2 d x = π 2 x 2 β d x = π 2 β 1 ( 1 x 2 β 1 ) 2 = V_{f} = \pi\int_{2}^{\infty} (f(x))^2 dx = \pi\int_{2}^{\infty} x^{-2\beta} dx = -\dfrac{\pi}{2\beta - 1}(\dfrac{1}{x^{2\beta - 1}})|_{2}^{\infty} = π ( 2 β 1 ) 2 2 β 1 \dfrac{\pi}{(2\beta - 1)2^{2\beta - 1}}

π ( 2 β 1 ) 2 2 β 1 = V g = π ( g ( x ) ) 2 d x = π a 2 ( a x + b ) 2 a d x = π a ( 1 a x + b ) 2 = π a ( 2 a + b ) \implies \dfrac{\pi}{(2\beta - 1)2^{2\beta - 1}} = V_{g} = \pi\int (g(x))^2 dx = \dfrac{\pi}{a}\int_{2}^{\infty} (ax + b)^{-2} * a \:\ dx = -\dfrac{\pi}{a}(\dfrac{1}{ax + b})|_{2}^{\infty} = \dfrac{\pi}{a(2a + b)}

a ( 2 a + b ) = ( 2 β 1 ) 2 2 β 1 \implies \boxed{a(2a + b) = (2\beta - 1) 2^{2\beta - 1}}

and

2 a + b = 2 β \boxed{2a + b = 2^{\beta}}

Solving the system we obtain:

a = ( 2 β 1 ) 2 β 1 a = (2\beta - 1)2^{\beta - 1} and b = 2 β + 1 ( 1 β ) g ( x ) = 1 2 β 1 ( ( 2 β 1 ) x 4 ( β 1 ) ) b = 2^{\beta + 1} (1 - \beta) \implies g(x) = \dfrac{1}{2^{\beta - 1}((2\beta - 1)x - 4(\beta - 1))}

V 1 ( β ) = π 2 ( f ( x ) ) 2 d x = π ( 2 β 1 ) 2 2 β 1 V_{1}(\beta) = \pi\int_{-\infty}^{-2} (f(x))^2 dx = \dfrac{\pi}{(2\beta - 1)2^{2\beta - 1}}

and

V 2 ( β ) = π 2 ( g ( x ) ) 2 d x = π a ( 1 a x + b ) 2 = π a ( 2 a b ) = π ( 2 β 1 ) 2 2 β 1 ( 4 β 3 ) V_{2}(\beta) = \pi\int_{-\infty}^{-2} (g(x))^2 dx = -\dfrac{\pi}{a}(\dfrac{1}{ax + b})|_{2}^{\infty} = \dfrac{\pi}{a(2a - b)} = \dfrac{\pi}{(2\beta - 1)2^{2\beta - 1}(4\beta - 3)}

V 1 ( β ) V 2 ( β ) = 4 ( β 1 ) π ( 2 β 1 ) ( 4 β 3 ) 2 2 β 1 = \implies V_{1}(\beta) - V_{2}(\beta) = \dfrac{4(\beta - 1)\pi}{(2\beta - 1)(4\beta - 3) 2^{2\beta - 1}} = 2 2 ( β 1 ) π ( 2 β 1 ) ( 2 2 β 3 ) 2 2 β 1 = α α ( β w ) π ( α β w ) ( α α β λ ) ( α α β w ) α + w + λ = 6 \dfrac{2^2(\beta - 1)\pi}{(2\beta - 1)(2^2\beta - 3) 2^{2\beta - 1}} = \dfrac{\alpha^{\alpha} (\beta - w)\pi}{(\alpha\beta - w)(\alpha^{\alpha}\beta - \lambda) (\alpha^{\alpha\beta - w})} \implies \alpha + w + \lambda = \boxed{6} .

Note: For β = 2 f ( x ) = 1 x 2 \beta = 2 \implies f(x) = \dfrac{1}{x^2} and g ( x ) = 1 6 x 8 V 1 ( 2 ) V 2 ( 2 ) = π 30 g(x) = \dfrac{1}{6x - 8} \implies V_{1}(2) - V_{2}(2) = \dfrac{\pi}{30} .

For β = 3 f ( x ) = 1 x 3 \beta = 3 \implies f(x) = \dfrac{1}{x^3} and g ( x ) = 1 20 x 32 V 1 ( 3 ) V 2 ( 3 ) = π 180 g(x) = \dfrac{1}{20x - 32} \implies V_{1}(3) - V_{2}(3) = \dfrac{\pi}{180} .

For trivial case β = 1 f ( x ) = g ( x ) = 1 / x \beta = 1 \implies f(x) = g(x) = 1/x and V 1 ( 1 ) = V 2 ( 1 ) = π 2 V_{1}(1) = V_{2}(1) = \dfrac{\pi}{2} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...